In vivo toxicological evaluation of graphene oxide nanoplatelets for clinical application - Amrollahi-Sharifabadi M (Dove Medical Press, 2018)
Mohammad Amrollahi-Sharifabadi,1 Mohammad Kazem Koohi,1 Ehsan Zayerzadeh,2 Mohammad Hassan Hablolvarid,3 Jalal Hassan,1 Alexander M Seifalian4 1Department of Basic Sciences, Faculty of Veterinary Medicine, University of Tehran, Tehran, Iran; 2Department of Biology, Faculty of Food Industry and Agriculture, Standard Research Institute, Karaj, Iran; 3Department of Pathology, Razi Vaccine and Serum Research Institute, Agricultural Research, Education and Extension Organization (AREEO), Karaj, Iran; 4NanoRegMed Ltd, Nanotechnology and Regenerative Medicine Commercialization Centre, The London BioScience Innovation Centre, London, UK Background: Graphene is considered as a wonder material; it is the strongest material on the planet, super-elastic, and conductive. Its application in biomedicine is huge, with a multibillion-dollar industry, and will revolutionize the diagnostic and treatment of diseases. However, its safety and potential toxicity is the main challenge.Methods: This study assessed the potential toxicity of graphene oxide nanoplatelets (GONs) in an in vivo animal model using systemic, hematological, biochemical, and histopathological examinations. Normal saline (control group) or GONs (3–6 layers, lateral dimension=5–10 µm, and thickness=0.8–2 nm) at dose rate of 50, 150, or 500 mg/kg were intraperitoneally injected into adult male Wistar rats (n=5) every 48 hours during 1 week to receive each animal a total of four doses. The animals were allowed 2 weeks to recover after the last dosing. Then, animals were killed and the blood was collected for hematological and biochemical analysis. The organs including the liver, kidney, spleen, lung, intestine, brain, and heart were harvested for histopathological evaluations.Results: The results showed GONs prevented body weight gain in animals after 21 days, treated at 500 mg/kg, but not in the animals treated at 150 or 50 mg/kg GONs. The biochemical analysis showed a significant increase in total bilirubin, with a significant decrease in triglycerides and high-density lipoprotein in animals treated at 500 mg/kg. Nonetheless, other hematological and biochemical parameters remained statistically insignificant in all GONs treated animals. The most common histopathological findings in the visceral organs were granulomatous reaction with giant cell formation and accumulation of GONs in capsular regions. Also, small foci of neuronal degeneration and necrosis were the most outstanding findings in the brain, including the cerebellum.Conclusion: In conclusion, this study shows that GONs without functionalization are toxic. The future study is a comparison of the functionalized with non-functionalized GONs. Keywords: graphene oxide, nanoplatelets, toxicity, preclinical, rat, histopathology, nanotechnology